Evaluasi Program Pencegahan Pelanggaran Netralitas ASN oleh Bawaslu Kota Serang pada Pemilu 2024 - Aji Sahyudi; Maulana Yusuf (HK Publishing, 2026)
Violations of civil servant (ASN) neutrality during the 2024 General Election positioned Serang City as the region with the highest number of cases in Banten Province, driven by the limited effectiveness of Bawaslu’s supervisory role in preventing ASN involvement in political activities, inadequate socialization and education on neutrality, and weak coordination with related institutions. This study evaluates the implementation of the ASN neutrality violation prevention program conducted by the Serang City Bawaslu during the 2024 Election using a descriptive qualitative approach and applying Leo Agustino’s policy evaluation framework, which covers aspects of human resources, institutional performance, facilities and technology, financial management, and regulation. Data were gathered through interviews, observation, and documentation. The findings indicate that the prevention program has been implemented fairly well, supported by competent, professional, and adaptive personnel with strong integrity. However, institutional effectiveness requires improvement, as coordination and collaboration with external stakeholders remain largely formal and insufficiently strategic. Participatory supervision through the Kader Pengawas Partisipatif (KPP) has not been optimal due to its incidental and unsustainable character. In addition, the utilization of communication media remains limited, budget management is still centralized under Banten Province Bawaslu, and specific technical guidelines at the local level are absent. This study underscores the need to strengthen institutional capacity and human resources, enhance inter-agency collaboration, develop innovative public communication strategies, and improve regulatory and budgetary support to ensure that ASN neutrality prevention efforts are implemented more effectively and sustainably.